Особливості навчальних програм з іншомовної підготовки здобувачів вищої освіти - Мунтян, Світлана Геннадіївна; Мунтян, Светлана Геннадиевна; Muntian, Svitlana (ТДАТУ, 2021)
The article analyses underlying features of foreign languages teaching syllabuses as the key component of the foreign languages teaching process planning as a whole. The article identifies the fundamental basis underpinning the syllabus design. Further, the article analyses the essence of the analytic, synthetic and functional approaches to the syllabus design, as well as respective syllabus types. The article identifies current models of foreign language application at a regional level, which are considered when designing respective syllabuses.
Keywords: foreign language teaching; syllabus design; synthetic approach; analytic approach; functional approach; type of syllabus